FCJ-168 Do objects dream of an internet of things? - Teodor Mitew (Fibreculture Journal, 2014)
This paper develops the notion of heteroclite sociable objects in the context of the emerging internet of things, and examines their transformative effect for understandings of sociability and agency. The notion of sociable objects attempts to capture the heterogeneous identity-shift occurring when heretofore obscure and mute objects ranging from toasters to thermostats acquire the agencies to leave semantically distinct traces online, and detour their human interlocutors into an object-mediated entanglement. Using a toolkit drawn from actor network theory and object oriented ontology, the paper discusses several examples illustrating the case for new parameters of sociability, better suited to a materiality acquiring conversational and anticipatory agencies.